Cardiac return assist blanket (CRAB) safely increases central venous pressure - Christopher Mitchell; Angela Jacques (Journal of International Medical Research)
Objective The cardiac return assist blanket (CRAB) has been designed to increase central venous pressure (CVP) to manage severe hypotension associated with anaphylaxis. This interventional study aimed to identify the relationship between CRAB pressure and CVP. CRAB pressure was also compared with the change in CVP associated with a straight leg raise (SLR), the Trendelenburg position, and 1 L of compound sodium lactate. Methods Sixteen healthy, fasted volunteers were exposed to CRAB pressure at 10, 20, 30, and 40 cmH 2 O, the SLR, and 15 degrees of the Trendelenburg position. The volunteers were then fed and hydrated with 1 L of CSL over 30 minutes and the protocol was repeated. Results The initial 10 cmH 2 O of CRAB pressure increased CVP by 3.7 mmHg (95% confidence interval 2.7, 4.7). Each subsequent 10-cmH 2 O rise in CRAB pressure increased CVP by 0.9 mmHg (95% confidence interval 0.55, 1.25). The SLR, Trendelenburg position, and 1 L of CSL increased CVP by 0.97 , 0.75 , and 0.69 mmHg, respectively. Conclusions The CRAB controllably increases CVP, and 40 cmH 2 O of CRAB pressure increases CVP by 6.41 mmHg. The effect of the CRAB is greater than that with the SLR, Trendelenburg position, or 1 L of CSL. This trial was registered with the ANZCTR (ACTRN12621000840886: https://www.anzctr.org.au ).